2021
DOI: 10.3390/su13105382
|View full text |Cite
|
Sign up to set email alerts
|

Design, Construction, and Curing Integrated Management of Defects in Finishing Works of Apartment Buildings

Abstract: The site analysis performed in the last ten years has found that building defects result from inconsistent decision-making and performance in the design, construction, and curing (DCC) processes. Therefore, for sustainable quality control, DCC integrated analysis and the management of causes by type and response measures should be in place. The objective of this study is to propose DCC integrated management of defects in finishing works of apartment buildings. To this end, the study surveyed 69,944 defects fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These factors are associated with poor workmanship and a lack of full-time quality assurance site supervisors. Poor workmanship is one of the most frequent factors identified as associated with both developing and developed countries (Forcada et al 2013b;Hamma-Adama et al 2020;Islam et al 2021b;Ismail et al 2015;Love and Edwards 2004b;Wasfy 2010;Yoon et al 2021), while poor site management and lack of supervision, or lack of skilled personnel at site for ensuring the required construction quality has been reported in several countries including Hong Kong, U.K., and Australia (Auchterlounie 2009;Hardie and Saha 2014;Sun and Meng 2009) -a particular problem in Bangladesh being private building owners cutting costs by dispensing with full-time supervision by a skilled team (Islam et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors are associated with poor workmanship and a lack of full-time quality assurance site supervisors. Poor workmanship is one of the most frequent factors identified as associated with both developing and developed countries (Forcada et al 2013b;Hamma-Adama et al 2020;Islam et al 2021b;Ismail et al 2015;Love and Edwards 2004b;Wasfy 2010;Yoon et al 2021), while poor site management and lack of supervision, or lack of skilled personnel at site for ensuring the required construction quality has been reported in several countries including Hong Kong, U.K., and Australia (Auchterlounie 2009;Hardie and Saha 2014;Sun and Meng 2009) -a particular problem in Bangladesh being private building owners cutting costs by dispensing with full-time supervision by a skilled team (Islam et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…The above discussion also pinpoints the research gap as the lack of a quantitative assessment of critical construction nonconformities in the densely populated South Asian developing countries, where poor workmanship, quality of materials, severe lack of the construction workers' knowledge and skills, and inadequate supervision and inspection (Islam et al 2021b) are potential causes of recent building collapses (Omondi 2019). A few studies collected data using questionnaire surveys or interviews and analyzed by descriptive statistics or the RII method (Tayeh et al 2020;Waziri 2016;Yoon et al 2021). Since expertjudgment-based data is subject to uncertainty, vagueness, and bias (Elbarkouky et al 2016;Islam et al 2019a;Novák 2006), a fuzzy-logic-based model such as the fuzzy group decision-making approach (FGDMA) can be potentially used to rank and analyze the critical nonconformities in building construction projects (Islam et al 2019a).…”
Section: Overview Of Nonconformity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Belmonte et al [20] validated an image analysis process (QSI) to evaluate the surface quality of self-compacting concrete that can be affected by trapped air holes in addition to other surface defects. Yoon et al [21] proposed the design, construction, and curing integrated management of defects in the finishing works of apartment buildings. This study showed that the proposed management method can be used as a basis for defect prevention measures for high-quality finishing work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the existing literature on finishing works focuses on managing the quality of finishing work in the design and construction process [18][19][20][21]. This is indirectly related to the various tasks of the maintenance phase, but there are limitations in managing the quality degradation problem of finishing components generated by various causes in the maintenance phase.…”
Section: Introductionmentioning
confidence: 99%